Perancangan Sistem Informasi E-Arsip Dokumen di Bappelitbang Kota Bandung Berbasis PHPRAD - Firman Ibrahim; Philip Broos; Candra Mecca Susyana; Muthmainnah (KITA Institute, 2023)
The purpose of this research is to create an E-Archive of Documents on Bappelitbang the City of Bandung, that serves as a system for collecting information in the form of documents that are stored using computer technology shaped the electronic document with the aim that the documents are easily viewed, managed, found and used again. The research method we apply is SDLC (Problem Indentification, Data Analysist, Application Design, Testing and Implementation. An E-Document Archive is a web-based as well as using PHPRAD as the application program as well as the XAMPP Server in the form of Apache and MySQL as server local. While the Navigation Structure is used as a flow of a program as well UML and DFD are used to represent the process flow of work between functions. The results of this study are to facilitate archiving activities that previously had to archive manually, which could cause data to be damaged or even lost which could be caused by excess storage, maintenance cocts, and other factors, but with the E-Archive Document the resulting performance becomes effective and efficient.